Programmed Cell Death in Asthma: Apoptosis, Autophagy, Pyroptosis, Ferroptosis, and Necroptosis - Liu L; Zhou L; Wang LL; Zheng PD; Zhang FQ; Mao ZY; Zhang HJ; Liu HG (Dove Medical Press, 2023)
Lu Liu,1,* Ling Zhou,1,* Ling-Ling Wang,1 Peng-Dou Zheng,1 Feng-Qin Zhang,1 Zhen-Yu Mao,1 Huo-Jun Zhang,2 Hui-Guo Liu1 1Department of Respiratory and Critical Care Medicine, Key Laboratory of Pulmonary Diseases of Health Ministry, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People's Republic of China; 2Department of Respiratory and Critical Care Medicine, Renmin Hospital of Wuhan University, Wuhan, People's Republic of China*These authors contributed equally to this workCorrespondence: Hui-Guo Liu; Huo-Jun Zhang, Email huiguol@163.com; hjzhang@whu.edu.cnAbstract: Bronchial asthma is a complex heterogeneous airway disease, which has emerged as a global health issue. A comprehensive understanding of the different molecular mechanisms of bronchial asthma may be an efficient means to improve its clinical efficacy in the future. Increasing research evidence indicates that some types of programmed cell death (PCD), including apoptosis, autophagy, pyroptosis, ferroptosis, and necroptosis, contributed to asthma pathogenesis, and may become new targets for future asthma treatment. This review briefly discusses the molecular mechanism and signaling pathway of these forms of PCD focuses on summarizing their roles in the pathogenesis and treatment strategies of asthma and offers some efficient means to improve clinical efficacy of therapeutics for asthma in the near future.Keywords: asthma, bronchial asthma, programmed cell death